2014
DOI: 10.1038/onc.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity of ADAM23 promotes tumor growth and metastasis through LGI4 and nitric oxide signals

Abstract: Intratumoral heterogeneity (ITH) represents an obstacle for cancer diagnosis and treatment, but little is known about its functional role in cancer progression. The A Desintegrin And Metalloproteinase 23 (ADAM23) gene is epigenetically silenced in different types of tumors, and silencing is often associated with advanced disease and metastasis. Here, we show that invasive breast tumors exhibit significant ADAM23-ITH and that this heterogeneity is critical for tumor growth and metastasis. We demonstrate that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Because we were unable to address ADAM23 methylation in the mesenchymal CTC subpopulation, we cannot exclude the possibility that differences in ADAM23 methylation in tumors of mesenchymal CTC‐positive and CTC‐negative patients could be associated with additional factors. In agreement with our hypothesis, Costa and coauthors showed in vitro and in vivo that ADAM23 intra‐allelic and intratumoral heterogeneity is critical for tumor growth and metastasis . They suppose that during metastatic progression, epigenetic instability may provide tumor cells with a growth advantage, leading to selection of clones with the densest methylation profiles .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Because we were unable to address ADAM23 methylation in the mesenchymal CTC subpopulation, we cannot exclude the possibility that differences in ADAM23 methylation in tumors of mesenchymal CTC‐positive and CTC‐negative patients could be associated with additional factors. In agreement with our hypothesis, Costa and coauthors showed in vitro and in vivo that ADAM23 intra‐allelic and intratumoral heterogeneity is critical for tumor growth and metastasis . They suppose that during metastatic progression, epigenetic instability may provide tumor cells with a growth advantage, leading to selection of clones with the densest methylation profiles .…”
Section: Discussionsupporting
confidence: 88%
“…They also showed that ADAM23 silencing can elicit a phenotypic switch from a proliferative to an invasive phenotype of tumor cells. Moreover, they showed that in ADAM23 heterotypic environments, cells without ADAM23 expression promote tumor growth and metastasis by enhancing the proliferation and invasivity of adjacent ADAM23‐positive cells …”
Section: Discussionmentioning
confidence: 99%
“…Addressing tumor microregional heterogeneity in time and space, the “multifaceted heterogeneity” of glioblastoma both between different tumors of similar H&E histology and within an individual tumor both in space and over time [3, 4]. A recent study of aggressive human breast cancers by Costa et al is exemplary of this phenomenon [5] that applies to glioblastoma. They demonstrated marked micro-regional heterogeneity within a single tumor mass with respect to a particular proteinase, ADAM-23, showing further that ADAM-23 positive and ADAM-23 negative subpopulations had different but mutually supporting functions [5].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of aggressive human breast cancers by Costa et al is exemplary of this phenomenon [5] that applies to glioblastoma. They demonstrated marked micro-regional heterogeneity within a single tumor mass with respect to a particular proteinase, ADAM-23, showing further that ADAM-23 positive and ADAM-23 negative subpopulations had different but mutually supporting functions [5]. Heterotypic environments create growth vigor in that ADAM-23 negative cells alone are invasion-competent but proliferation-poor while ADAM-23 positive subpopulations are proliferation-competent, invasion-weak [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation